Negative criticism and positive criticism in bastani –e- parizi historiography - Reza Shahmalaki; Koresh Fathi (تاریخ نگری و تاریخ نگاری, 2023)
Without ever claiming to be methodical in his individualistic historiography, Mohammad Ibrahim Bastani Parizi (1304-1391) repeatedly used negative criticism and ijtihad as well as positive criticism and ijtihad to disambiguate historical texts in all his works. The main question of this study is how Bastani Parizi used the weapon of historical criticism and ijtihad to infer the truth not mentioned in the sources and how this was reflected in his historiography. The results of this study will show that Bastani Parizi used negative criticism (ijtihad) and positive criticism (ijtihad) in all his famous works to respond to historical ambiguities and that he saw this technique as a way to achieve historical truth and objectivity. Thus, that it can be argued that this issue is the distinguishing feature and one of the most important features of his historiographical style. Accordingly, Bastani Parizi should be considered among the objectivist historians who believe that it is possible for a historian to achieve objectivity and historical truth in the light of historical criticism and ijtihad.